Mixed convection flows toward a stagnation-point on a stretching sheet - Aman, Fazlina; Ishak, Anuar (AENSI Publishing Corporation, 2010)
The problem of mixed convection stagnation-point flow of a viscous and incompressible fluid towards a stretching vertical sheet with prescribed surface heat flux is considered. The governing partial differential equations are first transformed into a system of ordinary differential equations, before being solved numerically by a finite-difference scheme known as Keller-box method. The features of the flow and heat transfer characteristics for different values of the governing parameters are analyzed and discussed. Both assisting and opposing flows are considered. The results indicate that dual solutions exist for the opposing flow, whereas for the assisting flow, the solution is unique.